The causal impact of childhood obesity on bone mineral density and fracture in adulthood: A two-sample Mendelian randomization study - Liang, Yuehui; Deng, Ming-Gang; Jian, Qinghong; Zhang, Minjie; Chen, Shuai (Frontiers in Nutrition, 2022)
Observational studies have indicated the associations between obesity with bone mineral density (BMD) and fracture but yield inconsistent results. The impact of childhood obesity on bone health in adulthood is even less clear. The present study adopted the Mendelian randomization methods to determine whether the genetically predicted childhood obesity was causally associated with BMD and the risk of fracture. Genetic variants were extracted from genome-wide association studies (GWAS) to identify childhood obesity loci [IEU open GWAS project: childhood obesity (ID: ieu-a-1096)] and single nucleotide polymorphisms (SNPs) as instrumental variables to investigate causality. We used two-sample univariable Mendelian randomization (MR) to estimate causal relationships between childhood obesity on BMD and fracture subtypes based on SNPs from European samples. To avoid bias, Cochran's Q test and leave-one-out variant analysis were performed. The MR analysis shows strong evidence that childhood obesity is causally associated with eBMD (OR 1.068, 95% CI 1.043–1.095, P < 0.001) and a weak decreased risk of leg fracture (OR 0.9990, 95% CI 0.9981–0.9999, P =0.033) based on the inverse variance weighting (IVW) method. After adjusting for diabetes and adult obesity, the results of eBMD remained the same. The MR analysis revealed sufficient evidence to indicate childhood obesity was causally associated with increased BMD and decreased risk of leg fracture in adults. Childhood obesity could be taken into consideration when assessing eBMD.